A basket of kola nuts - Bongasu-Tanla-Kishani (Langaa ; Distributed in N. America by Michigan State University Press, 2009)
Bold, original and stimulating in its inspirational insights, A Basket of Kola Nuts explores Cameroonís cultures as remarkable pivots of moral rectitude and such sickening vicious-circles as bribery and corruption. Ethnically grass-rooted and globalizing rather than alarmingly exotic and exclusive, this poetic diction of form-content aims at revitalizing its material contents to sever it from extinction and revamp cultural values that break the patience of silence to question deviation rather than the concrete interface of cultural identities and differences. Uprightly appealing, this poetry g.